2021
DOI: 10.1177/13591053211059393
|View full text |Cite
|
Sign up to set email alerts
|

Individual factors in the relationship between stress and resilience in mental health psychology practitioners during the COVID-19 pandemic

Abstract: Utilising an online survey, this study aimed to investigate the concurrent effects of pre-pandemic and COVID-19 stress on resilience in Mental Health Psychology Practitioners (MHPPs) ( n  = 325), focussing on the mediation effects of specific individual factors. Optimism, burnout and secondary traumatic stress, but not coping strategies, self-efficacy, compassion satisfaction, or self-compassion, mediated both the relationship between pre-pandemic stress and resilience and COVID-19 stress and resilience. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…To measure resilience, they used the Resilience Scale (RS-14) (Wagnild, 2009). Similarly to Panourgia et al. (2021), authors brought up the transactional theory of stress proposed by Lazarus and Folkman (1984) as the framework of this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure resilience, they used the Resilience Scale (RS-14) (Wagnild, 2009). Similarly to Panourgia et al. (2021), authors brought up the transactional theory of stress proposed by Lazarus and Folkman (1984) as the framework of this study.…”
Section: Resultsmentioning
confidence: 99%
“…To measure resilience, they used the Resilience Scale (RS-14) (Wagnild, 2009). Similarly to Panourgia et al (2021), authors brought up the transactional theory of stress proposed by Lazarus and Folkman (1984) as the framework of this study. Results showed a significant indirect (mediation) effect of levels of perceived stress on both physical and mental health components through self-efficacy and resilience.…”
Section: Presentation Of Findings Across Studiesmentioning
confidence: 99%
“…Similar patterns were found in studies in other cultural contexts. For example, a study in the UK indicated that COVID-19-related stress did not predict CS in mental health practitioners (Panourgia et al, 2021 ). A study in Israel also found that the elevation of the clinical workload did not contribute to lower satisfaction with the job among nurses during the COVID-19 pandemic (Savitsky et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that positive or negative coping strategies did not necessarily alleviate or exacerbate stress responses. For example, Panourgia et al [ 60 ] discovered that avoidance behavior can be an effective adaptive strategy in some situations, allowing people to deal with problems more quickly. Considering the complexity of the effects of coping, the ways in which coping and specific coping strategies function deserve further study.…”
Section: Limitationmentioning
confidence: 99%